The South Texas Health Status Review: A Health Disparities Roadmap - Ramirez, Amelie G.; Thompson, Ian M.; Vela, Leonel; Ramirez, Amelie G.; Thompson, Ian M.; Vela, Leonel; Ramirez, Amelie G.; Thompson, Ian M.; Vela, Leonel (Cham Springer Nature, 2013)
Public Health; Epidemiology; Demography
English
Keywords: Manufacturing industries; Pharmaceutical industries; Law; Public health & preventive medicine; Biochemical engineering; Public Health; Epidemiology; Demography